2000
DOI: 10.1002/1522-2675(20000705)83:7<1424::aid-hlca1424>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Fluorescent Nucleoside Analogue Benzo[g]quinazoline 2′-O-Methyl--D-ribofuranoside to Monitor the Binding of the HIV-1 Tat Protein or of Antisense Oligonucleotides to the TAR RNA Stem-Loop

Abstract: Dedicated to Prof. Dr. Frank Seela on the occasion of his 60th birthday The Tat protein is an essential trans-activator of HIV gene expression. It interacts with its RNA recognition sequence, the trans-activation responsive region TAR, as well as cellular factors. These interactions are potential targets for drug discovery against HIV infection. We have developed a new and sensitive assay for the measurement of Tat binding to TAR in solution under equilibrium conditions based on the change of fluorescence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Binding to the lower affinity site yielded an apparent microscopic K D of 300 ± 75 nM, and resulted in only a moderate decrease in fluorescence intensity. The observation of multiple binding events for Tat with ⌬TAR is consistent with previous studies (Weeks et al 1990;Weeks and Crothers 1992), and the observed K D 's fall within the range of those previously reported based on gel electrophoretic, filter, and fluorescencebinding assays performed under slightly different buffer, salt, and temperature conditions (Weeks et al 1990;Weeks and Crothers 1992;Churcher et al 1993;Arzumanov et al 2000). Titration of ⌬TAR-ap23 with the Tat peptide gave results that were quite similar to those described above, except that only about a fourfold initial increase in fluorescence intensity was observed before the latter began to decrease with increasing ligand concentration (data not shown).…”
Section: -Ap Fluorescence As a Probe Of Tar Interactionssupporting
confidence: 91%
See 2 more Smart Citations
“…Binding to the lower affinity site yielded an apparent microscopic K D of 300 ± 75 nM, and resulted in only a moderate decrease in fluorescence intensity. The observation of multiple binding events for Tat with ⌬TAR is consistent with previous studies (Weeks et al 1990;Weeks and Crothers 1992), and the observed K D 's fall within the range of those previously reported based on gel electrophoretic, filter, and fluorescencebinding assays performed under slightly different buffer, salt, and temperature conditions (Weeks et al 1990;Weeks and Crothers 1992;Churcher et al 1993;Arzumanov et al 2000). Titration of ⌬TAR-ap23 with the Tat peptide gave results that were quite similar to those described above, except that only about a fourfold initial increase in fluorescence intensity was observed before the latter began to decrease with increasing ligand concentration (data not shown).…”
Section: -Ap Fluorescence As a Probe Of Tar Interactionssupporting
confidence: 91%
“…To date, a few low molecular-weight compounds have been reported that block the Tat·TAR interaction in vitro with inhibition constants in the nano-to micromolar range (Mei et al 1995(Mei et al , 1997Hamy et al 1997Hamy et al , 1998Wang et al 1998;Sannes-Lowery et al 1999;Litovchick et al 2001;Du et al 2002;Lind et al 2002;Blount and Tor 2003;Hwang et al 2003;Davis et al 2004;Murchie et al 2004), some of which have also shown viral inhibition in cellular assays. Among these compounds are a number of amino acid and nucleotide analogs (Mestre et al 1999;Arzumanov et al 2000Arzumanov et al , 2001Mayhood et al 2000;Tamilarasu et al 2000) and aminoglycoside antibiotics (Mei et al 1995;Wang et al 1998;Blount and Tor 2003), which have been shown to effectively compete with Tat for binding to TAR. Studies have also focused on modifying and conjugating small molecules to enhance their specificity for TAR through directed and combinatorial chemical approaches (Hamy et al 1998;Gelus et al 1999;Litovchick et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the reverse situation compared with filter-binding experiments of Figure 2 Although the buffer conditions are not identical, it is of interest to note that the best 10-mer 1493 has a K d value (29 nM) similar to that previously measured by a direct equilibrium fluorescence method for a 12-mer OMe oligonucleotide binding to a stem-loop TAR RNA in a region with apical loop, double helix and internal bulge (approx. 20 nM) [34]. This suggests that the nucleotides bound within the A site may not be dissimilar in accessibility to those found within other structured RNAs and thus not significantly hindered by the overall 30 S ribosomal subunit nucleoprotein assembly.…”
Section: K D Measurements Of the Binding Of Ome Oligoribonucleotides mentioning
confidence: 83%
“…24,25 Similarly, a TAR construct containing benzo[g]quinazoline-2,4(1H,3H)-dione, a large U analogue, displayed changes in fluorescence upon Tat binding when incorporated in the U-rich bulge. 26 We have recently reported a series of responsive fluorescent pyrimidine nucleoside analogues functionalized at the 5-position with aromatic five-membered heterocycles. 27 A furancontaining uridine is particularly useful.…”
Section: Introductionmentioning
confidence: 99%